Analisis Permasalahan Kesuburan Tanah dan Strategi Pemulihannya di Desa Lawelu Kecamatan Ulu Moro’o Kabupaten Nias - Herman Saputra Ndruru; Mesrana Putri Lahagu; Ernidar Mendrofa; Helmin Parida Zebua (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
Soil fertility is one of the key factors in determining the success of the agricultural sector, especially in rural areas that rely heavily on agricultural products as the main source of livelihood. This research aims to analyze soil fertility problems and formulate strategies for its recovery in Lawelu Village, Ulu Moro'o Sub-district, Nias Regency. The approach used was descriptive qualitative with the support of quantitative data, through field observations, in-depth interviews, documentation studies, and questionnaire surveys of farmers. The results showed that the decline in soil fertility was caused by excessive use of chemical fertilizers, lack of crop rotation, and lack of sustainable agriculture education. Geographical factors such as high rainfall and steep topography also accelerated soil degradation. Recovery strategies are directed at a holistic approach through the application of organic fertilizers, biochar technology, crop rotation, soil and water conservation, and strengthening the role of local institutions and policies. These findings provide a foundation for the formulation of agricultural policies that are sustainable and contextualized in underdeveloped areas such as Lawelu Village.